Socioeconomic variations in risky sexual behavior among adolescents in 14 sub-Saharan Africa countries who report ever having had sex - Mohamed M. Ali; Leena Merdad; Saverio Bellizzi (BMC, 2021)
Abstract Background Equity is a guiding principle of the Global Strategy for Women, Children and Adolescents' Health (2016-2030) aimed at improving adolescent health and responding more effectively to adolescents' needs. We investigated the socioeconomic differentials in having multiple sexual partners and condom use among unmarried adolescents who reported ever having had sex aged 15-19 years in 14 sub-Saharan countries. Methods Using the most recent publicly available Demographic and Health Surveys conducted between 2011 and 2018, we calculated survey- and sex-specific proportions of two or more partners and condomless sex, both overall and by selected socioeconomic characteristics and we fitted logistic regression models to estimate the survey- and sex-specific adjusted odds ratios. The pooled adjusted odds ratios were estimated using multilevel logistic regression. Results In most countries, higher percentages of male adolescents than female adolescents reported having more than one partner in the last 12 months. Conversely, a lower percentage of young male reported having condomless sex when compared to young female: from 19.8% in Gabon to 84.5% in Sierra Leone among male adolescents and from 32.6% in Gabon to 93.2% in Sierra Leone among female adolescents. In the multilevel analyses, condomless sex was associated with place of residence, wealth and schooling for both female and male adolescents, while among male adolescents multiple partnerships was significantly associated with place of residence. Conclusion Our findings on disparities in condomless sex associated with socioeconomic characteristics might reflect constraint choice and decision making. Results also suggest the need for educational programming and services and better access to barrier methods.